Analisis Kelayakan Usaha Pembibitan Tanaman Durian Pada UD. Bayu Wira Tama di Kecamatan Ranomeeto Kabupaten Konawe Selatan - Aisyah, Tendri Nur; Abdullah, Weka Gusmiarty; Rianse, Ilma Sarimustaqiyma (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This study aims to determine the feasibility of the cultivation of durian plants in UD. Bayu Wira Tama in Ranomeeto Sub-district of South Konawe District. The study was conducted using case study method with business owner. UD.Bayu Wira Tama as the respondent. Data analysis used are R/C Ratio, capital productivity ( /C) Ratio, labor productivity, income, BEP Revenue, BEP Production, and BEP Price. The result of this research shows that the cultivation of durian plants. UD. Bayu Wira Tama in Ranomeeto Sub-district of South Konawe Regency is feasible to be operated with several indicators, namely R/C Ratio which shows the number of 7,35 > 1 (R/C Ratio >1), capital productivity ( C) Ratio of 6,15 % (( /C) Ratio > Current bank interest), labor productivity of Rp 201.149 (labor productivity > prevailing wage rate), income of Rp 30.000.000/ production period (income > land rent), BEP Rp 1.938.172 (acceptance > BEP acceptance), BEP production 96.9/tree (production > BEP production), and the price received by the nursery owner is bigger than BEP price ie Rp 20.000 > Rp 2.038 (Price > BEP Price)